Black Lives Matter: Gerakan Sosial dan Pengaruhnya Terhadap Kondisi Politik Amerika Serikat - Zikri Ahmad Azzam; Tedi Erviantono; Ni Wayan Radita Novi Puspitasari (Lembaga Pengembangan Kinerja Dosen, 2024)
This paper seeks to analyze the Black Lives Matter social movement that emerged from the anxiety of the American people towards various acts of racism that were rampant and even carried out by state officials. One of the most crowded cases was in 2018 when the arrest of George Floyd, who is black, experienced acts of violence committed by white police officers. Black Lives Matter began to emerge in 2013, becoming a form of community resistance that was initially initiated by three women from the black community who had a mission to eradicate white supremacy and build strength to overcome the rampant discrimination felt by the black race. The paper is wrapped in new social movement theory to help the author describe how Black Lives Matter became a small social movement that later went global and influenced political conditions in the United States.